Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Climate Change, Ocean Acidification and Sponges 2017
DOI: 10.1007/978-3-319-59008-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Fluxes and Ecological Functions of Coral Reef Sponges in a Changing Ocean

Abstract: Coral reefs are iconic examples of biological hotspots, highly appreciated because of their ecosystem services. Yet, they are threatened by human impact and climate change, highlighting the need to develop tools and strategies to curtail changes in these ecosystems. Remarkably, ever since Darwin's descriptions of coral reefs, it has been a mystery how one of Earth's most productive and diverse ecosystems thrives in oligotrophic seas, as an oasis in a marine desert. Sponges are now increasingly recognized as ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 193 publications
(295 reference statements)
9
140
2
Order By: Relevance
“…In addition to picoplankton, sponges also feed on dissolved organic matter (de Goeij, Lesser, & Pawlik, ). Although picoplankton increases with increasing depth (Lesser, ), both dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) decrease from shallow to mesophotic depths (de Goeij et al, ; Figure ). For both picoplankton and DOC/DON abundance, there are significant differences occurring at ~ 60 m, coincident with the most dramatic changes in sponge diversity and biomass (Lesser & Slattery, ) and changes in underwater irradiance (Lesser, ; Lesser et al, , ; Slattery & Lesser, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to picoplankton, sponges also feed on dissolved organic matter (de Goeij, Lesser, & Pawlik, ). Although picoplankton increases with increasing depth (Lesser, ), both dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) decrease from shallow to mesophotic depths (de Goeij et al, ; Figure ). For both picoplankton and DOC/DON abundance, there are significant differences occurring at ~ 60 m, coincident with the most dramatic changes in sponge diversity and biomass (Lesser & Slattery, ) and changes in underwater irradiance (Lesser, ; Lesser et al, , ; Slattery & Lesser, ).…”
Section: Discussionmentioning
confidence: 99%
“…For both picoplankton and DOC/DON abundance, there are significant differences occurring at ~ 60 m, coincident with the most dramatic changes in sponge diversity and biomass (Lesser & Slattery, ) and changes in underwater irradiance (Lesser, ; Lesser et al, , ; Slattery & Lesser, ). In particular, both DOC and POC sources do not appear to be limiting over the shallow to mesophotic depth range, whereas PON, in the form of picoplankton, increases and might close the C : N ratio sufficiently to promote increased sponge growth at mesophotic depths (de Goeij et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to POM resources, the trophic biology of sponges includes the consumption of DOM, specifically DOC (de Goeij et al. , , ), and recent observations have suggested that different species and/or communities of sponges consume different proportions of POM and DOM (Maldonado et al. , Hoer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rützler, 2002;López-Victoria and Zea, 2005;Ward-Paige et al, 2005;Schönberg and Ortiz, 2008;Carballo et al, 2013;Kelmo et al, 2013;Wisshak et al, 2014;Ramsby et al, 2017a) and of their potential role in phase shifts towards alternate steady or temporarily reversible states (Norström et al, 2009;González-Rivero et al, 2011a;Bozec et al, 2015;Chaves-Fonnegra et al, 2017). The prediction of increased abundance of bioeroding sponges is in accordance with a more general hypothesis of shifts towards sponge (and algae) dominated reef systems in the Caribbean and elsewhere, with important implications for nutrient cycling on coral reefs (Diaz and Rützler, 2001;Norström et al, 2009;McMurray et al, 2010;Colvard and Edmunds, 2011;Bell et al, 2013;Ruzicka et al, 2013;Villamizar et al, 2014;De Bakker et al, 2017;De Goeij et al, 2017). Recent studies have elucidated that both bottom-up (e.g.…”
Section: Bioerosion In the Context Of Global Changesupporting
confidence: 56%